The Turmeric in Cotton yarns dyeing by using Pisang Awak banana rubber as the mordant - รัชเวทย์ อโนดาษ์; กวางคำ จิรประภา; ใจนัน สุภาวรรรณ; ชาติอารยะวดี วิศณุสรรค์ (Progress in Applied Science and Technology, 2017)
In this research aimed to study the Turmeric dyed extraction process for using in dyeing the cotton yarns, cooperated with the Pisang Awak banana rubber as the mordant and to study in the optimum conditions in this dyeing process. In the Turmeric extraction process, water and ethanol used in extraction this dyed. After the wavelength investigated by UV-VIS spectroscopy found that the Turmeric ethanol extracted solution had a maximum absorption wavelength at 426 nm. The mordant, the Pisang Awak banana rubber, had used in different time of dyeing cotton yarns process (before, during and after) with Turmeric ethanol extraction. Moreover the different in temperatures (30 oC, 50 oC and 70 oC) and different time (30, 60 and 90 min) in dying process had studied. The optimum conditions was put the cotton yarns in the Pisang Awak banana rubber before dying in Turmeric ethanol extracted solution at 70 oC and 90 min, which the best dye absorption at 0.19 gram per the weight of the cotton yarns. After color fastness, washing test had undertaken, which using a standard detergent. The color of dyed cotton yarn were compared with the standard Grey Scales color plate. The findings was the cotton yarns color fastness tolerance to wash was at level five. This meant the dyed cotton yarn from Turmeric ethanol extracted dye has a high durable color strength value in washing with a code 2.5 Y 6/8. In the other hands, the study of the cotton yarns which dyed with Turmeric water extracted found that the mordant, the Pisang Awak banana rubber, could put in the solution after dying with Turmeric water extracted at 70 oC and 30 min. The color fastness tolerance to wash test was in the level five, means a high durable color strength value in washing with a code 2.5 Y 7/10 as well.